Ma’pa’tondokan Sebagai Model Korelasional Etis-Praktis Menurut Paul F. Knitter Dalam Dialog Interreligius Di Lembang Rumandan - Mangewa, Andri Susanto; Agasta, Ferialdi (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2024)
Living in harmony and peace between religious communities is something that everyone really desires. But in reality, certain areas still show disharmony which leads to conflict between religious communities. It seems different from this in Lembang Rumandan, Rano District, Tana Toraja. Life between religious communities is very harmonious and peaceful. This fact is measured by the behavior of the people who care about others even though they have different religions, as shown in the ma'pa'tondokan tradition, namely a tradition of mutual cooperation when a death ceremony (Rambu Solo') or a wedding party (Rambu Tuka') is held and other events. The whole community, regardless of religious differences, helps families who are holding an event. This research uses qualitative methods with a descriptive model and field research by interviewing several figures who are considered to have broad insight into this tradition. This research shows that ma'pa'tondokkan can be a bridge for dialogue between Muslims and Christians in Lembang Rumandan. This is because the values ​​contained in this tradition such as caring, solidarity, kinship can enable these two religious communities to know each other better.